Tc-99m-Labeled Iron Oxide Nanoparticles as Dual-Modality Contrast Agent: A Preliminary Study from Synthesis to Magnetic Resonance and Gamma-Camera Imaging in Mice Models - Karageorgou, MA; Rapsomanikis, AN; Mirkovic, M; Vranjes-Duric, S; Stiliaris, E.; Bouziotis, P.; Stamopoulos, D. (NANOMATERIALS, 2022)
The combination of two imaging modalities in a single agent has received increasing attention during the last few years, since its synergistic action guarantees both accurate and timely diagnosis. For this reason, dual-modality contrast agents (DMCAs), such as radiolabeled iron oxide (namely Fe3O4) nanoparticles, constitute a powerful tool in diagnostic applications. In this respect, here we focus on the synthesis of a potential single photon emission computed tomography/magnetic resonance imaging (SPECT/MRI) DMCA, which consists of Fe3O4 nanoparticles, surface functionalized with 2,3-dicarboxypropane-1,1-diphosphonic acid (DPD) and radiolabeled with Tc-99m, [Tc-99m]Tc-DPD-Fe3O4. The in vitro stability results showed that this DMCA is highly stable after 24 h of incubation in phosphate buffer saline (similar to 92.3% intact), while it is adequately stable after 24 h of incubation with human serum (similar to 67.3% intact). Subsequently, [Tc-99m]Tc-DPD-Fe3O4 DMCA was evaluated in vivo in mice models through standard biodistribution studies, MR imaging and gamma-camera imaging. All techniques provided consistent results, clearly evidencing noticeable liver uptake. Our work documents that [Tc-99m]Tc-DPD-Fe3O4 has all the necessary characteristics to be a potential DMCA.